Dynamic digital capabilities and supply chain resilience: The role of government effectiveness - Yogesh Dwivedi (International Journal of Production Economics, 2023)
Organizations in recent times are increasingly investing in building supply chain resilience following disruptions due to natural disasters, geo-political crises, and pandemics. A lack of government support has exacerbated the disruption to supply chains in some regions of the world. The positive influence of digitalization on social inclusion, government accountability, and creating a more open environment is well understood. Despite this, different countries have shown varying degrees of digital responsiveness during the pandemic as they attempted to deal with the effects of various COVID strains. The influence of government policies on the supply chain has not been examined in the literature so far and, hence, to address this research gap, we examine the interaction effect of government support effectiveness i.e., tax credits, interest deferral, digital investment, soft loans on dynamic capabilities i.e., digital adaptabilities and digital agilities and on supply chain resilience, using a multi-method approach. To understand how digital adaptability and agility improve supply chain resilience, we conducted 13 semi-structured interviews. Additionally, we pretested our measurement instrument using qualitative semi-structured interviews to validate our hypothesized relationships. We collected data at a specific point of time using a survey-based instrument (N = 203) to address our research questions. Based on data analyses of both the qualitative and survey-based data, our findings indicate that digital adaptability is an important driver of digital agility. Furthermore, the results indicate that government effectiveness is crucial to enhancing supply chain resilience by enhancing digital adaptability and agility. Our research makes some useful contributions to the dynamic capability view by enhancing theoretical understanding, of the role of government in building digital capabilities in uncertain times, to improve supply chain resilience. It also bridges the research gaps between macro and micro perspectives, as identified by management scholars. Lastly, we noted the weaknesses and limitations in the study and therefore we have offered multiple research directions forward, that could help researchers to further develop our current work.